The Effect of Financial Technology on the Performance of Micro, Small, and Medium Businesses - Sumani, Sumani; Prasetya, Ignatius Bryan (International Business Management - Universitas Ciputra, 2022)
Micro, small, and medium enterprises dominate the number of entrepreneurs in developing countries like Indonesia. Even though the scale enterprises are small, MSM entrepreneurs can’t be separated from tech- nology in the current era. Therefore, this study aims to analyze how finan- cial technology can affect the performance of Micro Small. and Medium Enterprises in Jakarta, Bogor, Depok, Tangerang and Bekasi. The data taken for this study is primary data obtained through the distribution of online questionnaires to MSM entrepreneurs in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The number of samples in this study was 130 respondents with a non-probability sampling method with purposive sampling technique. The research data that has been obtained were analyzed using SPSS 26 software. The results showed that the use of financial technology did not significantly affect the performance of MSMEs. Meanwhile, financial tech- nology funding, cash back, or promos on products sold affects the perfor- mance of MSMEs. Maybe, it should be Micro, small, medium.